Change in Police Organizations: perceptions, Experiences, and the Failure to Launch - Schafer, Joseph A. (Journal of contemporary criminal justice, 2017)
Studies and accounts of change in police organizations frequently emphasize case studies of specific efforts enacted during relatively discrete periods of time in one or a few agencies. The narratives often emphasize the success of change efforts or seek to explain why initiatives failed in the case study agency. While instructive, such accounts do not provide broader insights into successes and failures with change across longer periods of time, differing types of change, and diverse organizational contexts. Using survey data from mid-career police supervisors attending the FBI National Academy program, this study considers change experiences. In particular, consideration is given to the frequency of change, its results, and the factors associated with successful and failed outcomes.